Aldosterone-to-renin ratio depends on age and sex in children attending a clinic for cardiovascular risk assessment. Issue 2 (February 2018) - Genovesi, Simonetta; Antolini, Laura; Orlando, Antonina; Tassistro, Elena; Giussani, Marco; Nava, Elisa; Turolo, Lucia; Manolopoulou, Jenny; Parati, Gianfranco; Morganti, Alberto
Abstract : Objective: To determine plasma aldosterone concentration (PAC) and plasma renin concentration (PRC) and aldosterone-to-renin ratio (ARR) values in a population attending a Clinic for Cardiovascular Risk Assessment in Children. Methods: We assessed ARR and associated factors in a cohort of 287 children (137 female, 4–18 years). Weight and blood pressure (BP) were recorded. PAC (ng/dl) and PRC (mU/l) were measured using direct immunochemiluminescent assays. Data were examined by sex and according to four age classes. Results: Median PAC was similar from the youngest to the oldest age class ranging from 7.5 to 9.9 ng/dl in males and from 11.0 to 12.6 ng/dl in females. Median PRC was also similar across age classes in males ranging from 58.2 to 55.5 mU/l, whereas it progressively decreased from 61.5 to 36.6 mU/l in females ( P < 0.01). Median PRC was higher in prepubertal than in pubertal females only (53.6 vs. 40.2 mU/l, P < 0.03). As a result ARR was unchanged with increasing age in males (from 0.18 to 0.19), whereas in females it increased from 0.19 to 0.36 ( P < 0.03). After adjusting for body weight, BP and other possible confounders, age was inversely related with PRC and directly with PAC and ARR ( P < 0.001 for all), in females only. No relationship was found in both sexes between ARR values, BP, weight and family history of hypertension. Conclusion: In our children population, ARR is lower than in adults and diverges with increasing age between sexes, due to the age and puberty driven fall in PRC observed only in females. BP and weight are not associated with ARR distribution. Abstract : Supplemental Digital Content is available in the text